Veil and Vow : Marriage Matters in Contemporary African American Culture - Henderson, Aneeka A. (Book collections on Project MUSE., 2020)
"In 'Veil and Vow', Aneeka Ayanna Henderson places familiar, often politicized questions about the crisis of African American marriage in conversation with a rich cultural archive that includes fiction by Terry McMillan and Sister Souljah, music by Anita Baker, and films such as ###The Best Man#. Seeking to move beyond simple assessments of marriage as "good" or "bad" for African Americans, Henderson critically examines popular and influential late twentieth- and early twenty-first-century texts alongside legislation such as the 1996 Defense of Marriage Act and the Welfare Reform Act, which masked true sources of inequality with crisis-laden myths about African American family formation. Providing a new opportunity to grapple with old questions, including who can be a citizen, a "wife," and "marriageable," 'Veil and Vow' makes clear just how deeply marriage still matters in African American culture"--